Painting of fourth in genus Drosophila suggests autosome-specific gene regulation - Larsson, Jan (National Academy of Sciences, 2004)
Painting of fourth (POF) is a chromosome-specific protein in Drosophila and represents the first example of an autosome-specific protein. POF binds to chromosome 4 in Drosophila melanogaster, initiating at the proximal region, followed by a spreading dependent on chromosome 4-specific sequences or structures. Chromosome-specific gene regulation is known thus far only as a mechanism to equalize the transcriptional activity of the single male X chromosome with that of the two female X chromosomes. In Drosophila, a complex including the male-specific lethal proteins, “paints” the male X chromosome, mediating its hypertranscription, explained to some extent by the acetylation of lysine 16 on histone H4. Here, we show that Pof is essential for viability in both sexes and for female fertility. POF binding to an autosome, the F element, is conserved in genus Drosophila, indicating functional conservation of the autosome specificity. In three of nine studied species, POF binds to the male X chromosome. When bound to the male X, it also colocalizes with the dosage compensation protein male-specific lethal 3, suggesting a relationship to dosage compensation. The chromosome specificity is determined at the species level and not by the amino acid sequence. We argue that POF is involved in a chromosome-specific regulatory function.